Entrepreneurship Education and Entrepreneurial Interest Among Generation Z Students: An Experimental Study in Vocational Education - Hajar Dewantara; Nurhayani Nurhayani; Solomon Uchechukwu Eze (Universitas Negeri Makassar, 2026)
Entrepreneurship education has become an important strategy in developing entrepreneurial interest among Generation Z, particularly in vocational education environments that prepare students to face dynamic economic and business challenges. This study aims to examine the effect of entrepreneurship education on Generation Z’s entrepreneurial interest at SMK Negeri 4 Makassar using a True Experimental Design with a Post-Test-Only Control-Group Design approach. The study involved 40 students divided into an experimental group and a control group, with each group consisting of 20 respondents. The experimental group received entrepreneurship learning through an experiential-based approach, while the control group received conventional learning methods. Data were collected through questionnaires, observation, and documentation, and were analyzed using validity, reliability, normality, homogeneity, and t-test analyses. The findings indicate that entrepreneurship education has a positive and significant effect on entrepreneurial interest among Generation Z students. The experimental group demonstrated a higher increase in entrepreneurial interest compared to the control group after the learning intervention was implemented. The results also confirmed that the research instruments were valid and reliable, while the data fulfilled the assumptions of normality and homogeneity. The t-test analysis further demonstrated a statistically significant difference between both groups. This study contributes to the entrepreneurship education literature by providing empirical evidence through a true experimental approach, which remains relatively limited in previous studies. The findings imply that experiential entrepreneurship education can strengthen students’ motivation, confidence, and readiness to engage in entrepreneurial activities in the digital era.